Pengaruh Pengawasan Kerja Terhadap Produktivitas Kerja Karyawan Melalui Motivasi Kerja Pada CV. Pewarsa Ary Di Abiansemal Badung - Praba Anindita, I Gusti Ayu Mas Galuh; Sugianingrat, IAP Widani (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Human resources are one of the elements that have an important role in an organization. The better the human resources management in an organization, the higher the success rate of achieving company goals. The purpose of this study is to determine the effect of work supervision on employee work productivity through work motivation variables. This research was conducted on CV. Perwarsa Ary, located in Abiansemal, Badung with a total of 43 respondents. The data were analyzed using path analysis techniques, coefficient of determination, simultaneous significance test (F test), and partial test (T test) and path test with the help of SPSS for windows software. The results of this study found that work supervision had a positive and significant effect on employee productivity, Work Supervision has a positive and significant effect on Employee Work Motivation, Work Motivation has a positive and significant effect on Employee Work Productivity, and Work Motivation are able to mediate the effect of Work Supervision on Employee Work Productivity. Based on the results of data analysis, the better work motivation and work supervision, the better the work productivity of employees at CV. Pewarsa Ary.